Organización Contable en el Local Comercial “Home Atelier” de la ciudad de Loja. Periodo del 01 de julio al 31 de diciembre del 2019. - Padilla Armijos., Andrea Yajaira (2021)
The present thesis entitled, “ACCOUNTING ORGANIZATION IN THE COMMERCIAL PREMISES HOME ATELIER IN THE CITY OF LOJA. PERIOD FROM JULY 1 TO DECEMBER 31, 2019”, was developed with the purpose of proposing accounting tools that facilitate the owner, the generation of accounting information that allows knowing the real situation of the company and making the correct decision-making to improve business performance. When carrying out the accounting organization, each one of the objectives that were set was met; The process began with the survey of the initial inventory by means of the physical verification of the assets, values and obligations that the company maintained and preparation of the Initial Situation Statement; Auxiliary models were designed and used to record transportation expenses, deposits, accounts payable, payment roles, bank books, depreciation, Value Added Tax returns according to the documentation provided by the owner; the plan and account manual were designed, according to the needs of the company, with its description and the respective coding that facilitates the recording of operations; later the accounting process was developed starting with the initial inventory until concluding with the respective Financial Statements, the Daily Book was elaborated in which the transactions were recorded in chronological and systematic order applying the Multiple Account System; we continued with the preparation of the Ledger of each of the accounts implemented in the Daily Book to continue with the Trial Balance, the Worksheet and the Financial Statements: Balance, Income Statement, Cash Flow Statement; where timely and objective information on the situation of the company during the accounting period was reflected. Finally, in order to know and evaluate the economic and financial situation of the business, the application, calculation and interpretation of the financial indicators were carried out with the values reflected in the statements financial obtained; When applying the liquidity indicators, a working capital of 5 $98,355.79 was obtained, which means that the company has said amount to make investments; In the activity indicators, an inventory turnover of 0.50 times was obtained because the company maintains merchandise that has not been sold during the accounting period; and, in the indebtedness indicator, it obtains a percentage of 29.71 because the company has loans in financial institutions. The HOME ATELIER company presents during the six months a loss of $3,680.69 which is reflected in the financial statements and this is due to various factors such as the informal market, the smuggling of inferior quality merchandise among others; generating an oversupply, making it difficult for the company to compete in the medium, therefore its sales have decreased compared to the fixed expenses that it must maintain to persevere with the formality.